1981
DOI: 10.1093/geronj/36.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Skin Potential Level: Age and Recording Site Interactions

Abstract: Two experiments comparing the skin potential level (SPL) of young (30 to 47 years), middle-aged (48 to 65 years), and old (66 to 82 years) men during rest and during stimulus presentations using a nonhydrating electrolyte medium demonstrated that there was an ordered relationship between SPL negativity and age with the older men having less negative levels. Age differences in SPL were dependent upon recording site with larger age differences occurring when SPL was recorded from the medial phalanx than when SPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…A number of studies have shown that skin conductance levels are reduced in older individuals, associated perhaps with the decline in the number of active sweat glands and decreased output per sweat gland with age (Juniper & Dykman, 1967; MacKinnon, 1954). The magnitude of these age differences may be related to the anatomical location from which skin conductance is measured (Capriotti, Garwood, & Engel, 1981).…”
Section: Age Differencesmentioning
confidence: 99%
“…A number of studies have shown that skin conductance levels are reduced in older individuals, associated perhaps with the decline in the number of active sweat glands and decreased output per sweat gland with age (Juniper & Dykman, 1967; MacKinnon, 1954). The magnitude of these age differences may be related to the anatomical location from which skin conductance is measured (Capriotti, Garwood, & Engel, 1981).…”
Section: Age Differencesmentioning
confidence: 99%
“…Hypothesis 1: Older adults will exhibit reduced physiological response and faster recovery to stimuli as compared to younger adults Consistent with previous research, younger and older adult participants did not differ in baseline measures of HR, SCL, or SCR (Capriotti et al, 1981;Faucheux, Dupuis, et al, 1983;Garwood et al, 1982;Jennings et al, 1990;Shmavonian, et al, 1970), but did differ in baseline blood pressure readings, with older adults exhibiting significantly greater blood pressure (systolic and diastolic) at baseline than younger adults (Boutcher & Stocker, 1996;Garwood et al, 1982;Jennings et al, 1990). This latter finding supports literature suggesting the reduced plasticity of the arteries as a consequence of the aging process, resulting in greater peripheral resistance and higher resting blood pressure.…”
Section: Discussionsupporting
confidence: 67%
“…Despite methodological concerns, the internal validity of the remaining nine articles were sufficiently intact to warrant discussion of reported results, albeit with caution (Boutcher & Stocker, 1996;Capriotti, Garwood, & Engel, 1981;Faucheux, Baulon et al, 1983;Faucheux, Dupuis, Baulon, Lille, & Bourliere, 1983;Garwood, Engel, & Capriotti, 1982;Jennings, Brock, & Nebes, 1990;Shmavonian, Miller, & Cohen, 1968Shmavonian, Yarmat, & Cohen, 1965). It should be noted that technically, only the findings from six studies will be discussed because three of the nine articles included duplicate reports based on data presented in one of the other studies (Capriotti et al, 1981;Faucheux, Baulon, et al, 1983;Faucheux, Dupuis, et al, 1983;Garwood et al, 1982;Shmavonian et al, 1968Shmavonian et al, , 1970. Again, the findings from these six studies should be interpreted with caution because they, too, may also have some problems with limited generalizability and the threat of confounding variables, although not as problematic as in the other eleven studies.…”
Section: Psychophysiological Responses Of Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation